Manajemen Laba : Good Corporate Governance, Budaya Nasional & Korupsi Dalam Agency Cost - Andi Muh Syukur Hidayatullah; Abdul Hamid Habbe; Syamsuddin Syamsuddin (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
Agency Theory explains that company owners will incur agency costs to maintain the relationship between capital owners and management due to information asymmetry present in the company, one of which is earnings management practices. In line with research by Schwartz (1999) and Lacker & Tayan (2011), the policy of protecting assets owned by investors is determined by the quality of the legal system in force in a country and has direct implications for agency costs that must be incurred by investors. The implementation of Good Corporate Governance through an independent board of directors and audit committee policy provides improved corporate governance and early protection in the company so that the company's objectives are aligned with the objectives of the owners of capital. The purpose of this study is to determine and analyze the effect of the level of agency costs based on national cultural scores and the level of corruption, the role of independent boards of directors and independent audit committees on earnings management practices in companies listed on the Indonesia, Malaysia, Singapore, Philippines and Thailand stock exchanges in 2017 - 2019. The research data were obtained from the annual report reported by each company, and Hofstede's national culture score and the level of corruption perception issued by Tranparency International. This research is quantitative research with data analysis using multiple linear regression analysis. The results showed that the level of agency costs owned by a country had no significant effect on earnings management practices, while the independent board of directors and independent audit committee had a significant effect on earnings management practices and simultaneously agency costs, independent board of directors, and independent audit committee had a significant effect on earnings management practices. So it can be concluded that in dealing with agency problems, companies need to improve good corporate governance to support agency costs incurred by company owners in connection with preventing earnings management practices.